94.9k views
2 votes
Solve the following
2(x+3)=x-4

2 Answers

4 votes

Answer:

-10

Explanation:

2(x+3)=x-4

2x+6=x-4

2x-x=(-4)-6

x=-10

Hence the answer is -10

User ShpielMeister
by
5.4k points
2 votes

Answer:

x = - 10

Explanation:

2(x + 3) = x - 4 ← distribute parenthesis on left side

2x + 6 = x - 4 ( subtract x from both sides )

x + 6 = - 4 ( subtract 6 from both sides )

x = - 10

User David Sickmiller
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.